Transabdominal ultrasound accurately identifies a significant iliac vein area-reducing lesion in patients with pelvic venous insufficiency - Calcagno, Tess; Sulakvelidze, Levan; Kennedy, Richard; Christophi, Costas A.; Lakhanpal, Gaurav; Lakhanpal, Sanjiv; Pappas, Peter J (My University, 2023)
In patients with pelvic venous disorders secondary to pelvic venous insufficiency (PVI), the optimal imaging modality is ill-defined. Transabdominal ultrasound (TAU) is widely used to identify the presence of iliac vein stenosis. The purpose of the present investigation is to determine the accuracy of TAU for determining the presence of an iliac vein area-reducing lesion compared with intravascular ultrasound (IVUS).
Keywords: Pelvic venous insufficiency; Transabdominal ultrasonography